2000
DOI: 10.1103/physrevd.62.043008
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization group improved black hole spacetimes

Abstract: We study the quantum gravitational effects in spherically symmetric black hole spacetimes. The effective quantum spacetime felt by a point-like test mass is constructed by "renormalization group improving" the Schwarzschild metric. The key ingredient is the running Newton constant which is obtained from the exact evolution equation for the effective average action. The conformal structure of the quantum spacetime depends on its ADM-mass M and it is similar to that of the classical Reissner-Nordström black hole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
973
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 537 publications
(1,040 citation statements)
references
References 29 publications
63
973
4
Order By: Relevance
“…Recently a lot of work went into the exploration of the Wilsonian renormalization group (RG) flow of Quantum Einstein Gravity [1,2,3,4,5,6,7,8,9] and its possible impact on black holes and cosmology [10,11,12,13,14,15,16]. By definition, Quantum Einstein Gravity (QEG) is the conjectured quantum field theory of the spacetime metric whose bare action is (infinitesimally close to) an ultraviolet (UV) attractive non-Gaussian fixed point of the RG flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a lot of work went into the exploration of the Wilsonian renormalization group (RG) flow of Quantum Einstein Gravity [1,2,3,4,5,6,7,8,9] and its possible impact on black holes and cosmology [10,11,12,13,14,15,16]. By definition, Quantum Einstein Gravity (QEG) is the conjectured quantum field theory of the spacetime metric whose bare action is (infinitesimally close to) an ultraviolet (UV) attractive non-Gaussian fixed point of the RG flow.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Robertson-Walker spaces it will be shown that due to the very high degree of symmetry of the spacetime, the time-scale defined by "Hubble parameter" behaves essentially like the characteristic time scale associated to the relevant curvature invariants [38][39][40]. In the case of spherically symmetric spacetimes [30,31,41,42], near the singularity the proper distance of a radially free falling observer behaves essentially as 1/ √ Ψ 2 , being Ψ 2 the "Coulombian" component of the Weyl tensor.…”
Section: Pos(claqg08)008mentioning
confidence: 99%
“…In [30], a "RG-improvement" of the Schwarzschild metric has been performed and the properties of the corresponding "quantum black hole" have been explored. The improvement was based upon the scale dependent ("running") Newton constant G(k) obtained from the exact RG equation…”
Section: Rg Improved Black Hole Spacetimesmentioning
confidence: 99%
See 2 more Smart Citations